Iowa RBA, May 12, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for May 12, 1997. Highlights of the update include sightings of a Black-throated Gray Warbler and nesting Black-billed Magpies as well as the continued presence of a White-winged Dove. There were numerous other observations, including a Prairie Warbler, a Marbled Godwit, a light-phase Ferruginous Hawk, a Red-throated Loon, and a Pacific Loon. Also included are handwritten notes for the next week's update with sightings of a Western Tanager and a Fish Crow. Epson - sheet feed/flatbed